1998
DOI: 10.2337/diabetes.47.10.1643
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of insulin resistance in metabolic disorders: the Bruneck Study.

Abstract: The prevalence of insulin resistance in the most common metabolic disorders is still an undefined issue. We assessed the prevalence rates of insulin resistance in subjects with impaired glucose tolerance (IGT), NIDDM, dyslipidemia, hyperuricemia, and hypertension as identified within the frame of the Bruneck Study. The study comprised an age- and sex-stratified random sample of the general population (n = 888; aged 40-79 years). Insulin resistance was estimated by homeostasis model assessment (HOMA(IR)), preli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
466
4
33

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 755 publications
(527 citation statements)
references
References 0 publications
24
466
4
33
Order By: Relevance
“…27 Indeed, published data on children and adults have shown that all elements of the metabolic syndrome deteriorate with increasing obesity independently of sex, age and maturation status. 27,28 On the same issue, the decrease in the prevalence of overweight and obese girls at TP 4 Fdespite the overall sample increase in BMI and adiposity across timeFsuggests that children who are at the 'unhealthy' end of the BMI spectrum do not necessarily remain in the same category throughout adolescence. This positively surprising finding may be a recent development due to public awareness raised from publications showing that Greek children and adolescents demonstrate increased prevalence of obesity, 11,24 decreased physical activity levels 11,29 and, compared with their European and North American counterparts, low aerobic fitness levels.…”
Section: Discussionmentioning
confidence: 99%
“…27 Indeed, published data on children and adults have shown that all elements of the metabolic syndrome deteriorate with increasing obesity independently of sex, age and maturation status. 27,28 On the same issue, the decrease in the prevalence of overweight and obese girls at TP 4 Fdespite the overall sample increase in BMI and adiposity across timeFsuggests that children who are at the 'unhealthy' end of the BMI spectrum do not necessarily remain in the same category throughout adolescence. This positively surprising finding may be a recent development due to public awareness raised from publications showing that Greek children and adolescents demonstrate increased prevalence of obesity, 11,24 decreased physical activity levels 11,29 and, compared with their European and North American counterparts, low aerobic fitness levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there are considerable variations between individuals in the level of adiposity at which insulin resistance is exhibited; some relatively lean individuals are insulin resistant, whereas some very obese individuals are not (52) . Obese individuals who present as 'metabolically normal' are of considerable interest, with 16·6 % of obese adults categorised as metabolically healthy using relatively stringent criteria (53) .…”
Section: Statistical Considerations: the Reversal Paradoxmentioning
confidence: 99%
“…4 Grundy has suggested using hypertriglyceridaemia as a lead to identify the patients susceptible to insulin resistance. 5 Bonora et al 6 showed that the prevalence of insulin resistance increased two-fold to around 60% in hypertensive subjects combined with other components of the insulin resistance syndrome. About 30% of hypertensive patients were reported to have fasting triglyceride (TG) levels higher than 2.26 mmol/L.…”
Section: Introductionmentioning
confidence: 99%